304 IMPLEMENTING A FRAILTY SPECIFIC PHARMACY PRIORITISATION TOOLKIT IN AN OLDER PERSONS' REHABILITATION UNIT. (25th October 2022) - O'Reilly, A; McKenna-Barry, M; Kennedy, N; Ryan, S; O'Reilly, A; Donnellan, C; Pillay, I
Abstract: Background: Standardised identification of patients for medication review using nurse-delivered, frailty-specific pharmacy prioritisation toolkits should maximise effective use of limited pharmacy resources. A frailty-specific pharmacy prioritisation toolkit was introduced in a 21 bed older persons' rehabilitation unit to standardise pharmacy referrals and categorise the interventions made. Methods: The frailty-specific pharmacy prioritisation toolkit was applied to consecutive patients by upskilled rehabilitation nurses to identify patients for weekly senior pharmacist review over a 5-month period from 18th Jan 2022 to 24th May 2022. Regular use of high-risk medication, greater than 10 medications, patients with specific pharmaceutical concerns such as a desire to reduce their medication burden, acute or chronic kidney injury and admission potentially related to medications or admission with non-mechanical falls are included in this toolkit. Pharmacist interventions included recommendations on medications to be weaned or stopped, dose-adjusted, started or restarted and identification of prescribing errors. Age, gender and interventions were recorded onto Excel and data was analysed using descriptive statistics. Results: The total number of patients screened was 82. Eighty five percent (n=70) fulfilled criteria for a medication review. Mean age (SD) was 77(10.9) years. Female:male ratio was 1.5:1. Review was completed in 50% (n=35) of these cases. In total there were 228 interventions, with a mean (SD) of 6.5 (2.4) per patient. Eighty-four recommendations were made to wean or stop medication and thirty to dose adjust, of which 60% (n=18) were proton pump inhibitor dose reduction. Thirty-eight were to start or restart a medication, 34% (n=13) of which were for bone protection. Eleven prescribing errors were identified. Conclusion: The pharmacy prioritisation toolkit applied by existing rehabilitation nurses successfully identified patients for medication review. The review rate reflects a need for a twice-weekly senior pharmacy resource.